AKTIVITAS ANTIOKSIDAN, PROFIL ASAM AMINO DAN KUALITAS MIKROBA BEBONTOT DAGING AYAM PRODUK FERMENTASI TRADISIONAL BALI - Okarini I. A.; H. Purnomo; Aulanni'am .; L. E. Radiati (Fakultas Peternakan Universitas Udayana, 2019)
Antioxidant activity, amino acids profile and microbial quality of raw bebontot of chicken meat of spent laying henwere investigated. The samples were prepared using meat dices (1.5 x 2.0 cm) mixed with fresh ground coriander,garlic, galangal, white pepper, salt, sugar and coconut oil then wrapped in Areca catechu palm dried sheaths andfinally fermented spontaneously by drying under the sun for 5 days. The results showed there was a decreasing inpH value, moisture content and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity of final products, whileits total phenolic content was increasing. Glutamic acid was the most abundant amino acid in products after 5days fementation, followed by tyrosine, aspartic acid, lysine, leucine and histidine. The total plate count and lacticacid bacteria counts were decreasing to 9.39 log cfu/g and 8.98 log cfu/g; the Micrococcaceae was decreased to5.31 log cfu/g; the yeast and moulds counts were increased to 8.58 log cfu/g and 6.51 log cfu/g at the final stageof fermentation. It can be concluded that bebontot chicken meat in this study is a good source of natural phenolicantioxidant, and the present microorganisms will provide the source for the selection of strains well adapted to theenvironment and able to compete with contaminant bacteria.